The inter-rater reliability of the 13-point manual muscle test in people with spinal cord injury. (3rd October 2021) - Bye, Elizabeth; Glinsky, Joanne; Yeomans, Jayne; Hungerford, Amy; Patterson, Helen; Chen, Lydia; Harvey, Lisa
ABSTRACT: Objective : To determine the inter-rater reliability of the 13-point manual muscle test (MMT) in two upper limb muscle groups of people with tetraplegia Setting : The study was conducted at three spinal cord injury (SCI) units. Participants : Sixty people with complete or incomplete tetraplegia. Methods : The inter-rater reliability of the 13-point MMT was investigated. Strength of the elbow flexors and/or wrist extensors in people with tetraplegia was measured by two physiotherapists on the same day. Results : The weighted kappa coefficient (95% confidence interval) reflecting the agreement between the two strength assessments by two different assessors for the wrist extensors and elbow flexors were 0.96 (0.93 to 0.99) and 0.94 (0.89 to 0.99), respectively. Repeat measurements by different physiotherapists were within 1 of 13 points of each other 82% of the time for wrist extensors and 87% of the time for the elbow flexors. Conclusion : The 13-point MMT is a reliable measure of strength in the wrist extensors and elbow flexors of people with tetraplegia.